Pengembangan Sistem E-Commerce untuk Peningkatan Pengelolaan Data dan Transaksi di Kraptentik - Triawan Bigwanto; Mochamad Rafli Aditya; Muhammad Naufal Zharfan; Zulfadiandre Zulfadiandre; Galih Setiawan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This paper discusses the development of an E-Commerce system for Kraptentik to improve data and transaction management. Originally a wooden accessory craft center, Kraptentik has integrated new materials but faces challenges with outdated, non-computerized data management. A Point of Sales (POS) system was developed by ITENAS Informatics students to address these issues, aiming to enhance efficiency, data security, and business growth. The paper outlines the system’s design, implementation, and outcomes.